F‐18 FDG‐PET predicts outcomes for patients receiving total lymphoid irradiation and autologous blood stem‐cell transplantation for relapsed and refractory Hodgkin lymphoma. (15th March 2014) - Gentzler, Ryan D.; Evens, Andrew M.; Rademaker, Alfred W.; Weitner, Bing B.; Mittal, Bharat B.; Dillehay, Gary L.; Petrich, Adam M.; Altman, Jessica K.; Frankfurt, Olga; Variakojis, Daina; Singhal, Seema; Mehta, Jayesh; et al.
Summary Total lymphoid irradiation (TLI) followed by high‐dose chemotherapy and autologous haematopoietic stem cell transplant (aHSCT) is an effective strategy for patients with relapsed/refractory classical Hodgkin lymphoma (HL). We report outcomes for patients with relapsed/refractory HL who received TLI followed by high‐dose chemotherapy and aHSCT. Pre‐transplant fludeoxyglucose positron emission tomography (FDG‐PET) studies were scored on the 5‐point Deauville scale. Of 51 patients treated with TLI and aHSCT, 59% had primary refractory disease and 63% had active disease at aHSCT. The 10‐year progression‐free survival (PFS) and overall survival (OS) for all patients was 56% and 54%, respectively. Patients with complete response (CR) by PET prior to aHSCT had a 5‐year PFS and OS of 85% and 100% compared to 52% and 48% for those without CR (P = 0·09 and P = 0·007, respectively). TLI and aHSCT yields excellent disease control and long‐term survival rates for patients with relapsed/refractory HL, including those with high‐risk disease features. Achievement of CR with salvage therapy is a powerful predictor of outcome.